(untitled) (Rajarshi Janak University Research Journal, 2024)
The article is primarily dedicated to the Buddhism in action, ’the engaged Buddhism’. The roots of engaged Buddhism and its evolution and practice from the ancient time to the modern era have been reviewed. Though majority of researchers tend to link engaged Buddhism with the original philosophy of Buddhism, some of the researchers differ and try to emphasize that the idea of engaged Buddhism is against Buddhist’s original philosophy. Despite differing views on the origin of engaged Buddhism, the modern practice of engaged Buddhism round the globe has been found more advantageous for the better societies and better world than ever before.